2017
DOI: 10.1186/s40200-016-0278-y
|View full text |Cite
|
Sign up to set email alerts
|

Does honey have any salutary effect against streptozotocin - induced diabetes in rats?

Abstract: BackgroundDiabetes is a global, growing and costly public health problem. In the literature, there are conflicting reports on the effect of consumption of bee honey on diabetes. We assessed the possible effect of a commercially available bee honey (given orally by gavage at doses of 1 g/kg/day for 4 weeks) on the blood concentrations of glucose, insulin and leptin and body weight of rats with streptozotocin-induced diabetes.MethodsThirty-six rats were allocated randomly into six groups equally and treated for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The present study's results are consistent with Ahmed et al (2022), 21 who reported that feeding honeybees exacerbate blood glucose concentrations in STZ rats significantly. Al Aamri and Ali (2017) 37 conducted a study that revealed that the consumption of honeybee did not significantly impact body weight, glucose concentrations, or insulin concentrations. Abdul Sani and his colleagues (2014) 38 found that combining honeybee and ginger did not significantly impact blood glucose concentrations in STZ mice.…”
Section: Discussionmentioning
confidence: 99%
“…The present study's results are consistent with Ahmed et al (2022), 21 who reported that feeding honeybees exacerbate blood glucose concentrations in STZ rats significantly. Al Aamri and Ali (2017) 37 conducted a study that revealed that the consumption of honeybee did not significantly impact body weight, glucose concentrations, or insulin concentrations. Abdul Sani and his colleagues (2014) 38 found that combining honeybee and ginger did not significantly impact blood glucose concentrations in STZ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Honey (Aamri & Ali, 2017 ; Erejuwa et al, 2011 ) and STZ (Aamri & Ali, 2017 ) dosages were determined based on past dose–response effects and early investigations, and distilled water dose was chosen based on a previous study (Aamri & Ali, 2017 ).…”
Section: Methodsmentioning
confidence: 99%